Texture dependent lattice strains and texture gradient in AI7020. Issue 1 (April 2015) - Zhong, Z Y; Brokmeier, H-G; Maawad, E; Schell, N
Abstract: Firstly, an Al7020 block was characterized by the texture gradient, which was remarkably strong. Texture sharpness in the center with about 30 mrd (multiple random distribution) shows typical plain strain texture components. On the surface and close to the surface the texture sharpness is much weaker showing also shear components. Strongest shear was not directly at the surface but 4 mm deeper. The texture analysis at HEMS Beamline (Petra III/DESY-Hamburg) was done with continuous scanning mode to include all grains to improve the grain statistics. Secondly, with an in situ synchrotron experiment the texture dependent lattice strain behavior was investigated using flat tensile samples oriented 0°, 45° and 90° to the rolling direction (RD). Texture induced anisotropy influenced on the lattice dependent yield strength and the lattice dependent stress-strain behavior, which will be discussed in detail. Due to the high energy synchrotron beam complete Debye-Scherrer rings were obtained so that the patterns, parallel and perpendicular to loading direction (LD), were obtained simultaneously.